2021
DOI: 10.1093/comnet/cnaa028
|View full text |Cite
|
Sign up to set email alerts
|

Hypergraphs for predicting essential genes using multiprotein complex data

Abstract: Protein–protein interactions are crucial in many biological pathways and facilitate cellular function. Investigating these interactions as a graph of pairwise interactions can help to gain a systemic understanding of cellular processes. It is known, however, that proteins interact with each other not exclusively in pairs but also in polyadic interactions and that they can form multiprotein complexes, which are stable interactions between multiple proteins. In this manuscript, we use hypergraphs to investigate … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…Proteins interact with one another to form complex molecules that are essential to cell structure and function. The specific combination of these proteins can create very different resulting molecules, and combinations of more than two proteins can form a higher-order interaction network with vastly different topology than the equivalent pairwise network [ 51 , 52 ], suggesting that the structure of protein networks may vary significantly across interaction sizes.…”
Section: The Filtering Approachmentioning
confidence: 99%
“…Proteins interact with one another to form complex molecules that are essential to cell structure and function. The specific combination of these proteins can create very different resulting molecules, and combinations of more than two proteins can form a higher-order interaction network with vastly different topology than the equivalent pairwise network [ 51 , 52 ], suggesting that the structure of protein networks may vary significantly across interaction sizes.…”
Section: The Filtering Approachmentioning
confidence: 99%
“…As an alternative, they have proposed an intermediate optimal solution that interpolates between graph and hypergraph approaches and allows to better capture the importance of small molecules involved in many distinct reactions. More recently, Klimm et al [688] have used hypergraphs to investigate multiprotein complex data, showing how a pairwise (network) projection produces a hierarchical structure, that is instead not observed when polyadic interactions are considered. After comparing the protein complexes with appropriate null models, the authors found that larger complexes tend to be more essential, with a hyperdegree that better correlates with gene-essentiality information than the standard graph degree.…”
Section: Other Biological Systemsmentioning
confidence: 99%
“…It designs a hyperedge convolution operation to leverage the high-order correlations across data. Since then, a variety of hypergraph neural networks have been proposed for different learning tasks, including but not limited to image retrieval (Zeng et al 2023), quadratic assignment problem (Wang, Yan, and Yang 2021), biomedical science (Klimm, Deane, and Reinert 2021;Saifuddin et al 2022), keypoint matching (Kim et al 2022) and node classification (Bai, Zhang, and Torr 2021;Gao et al 2022).…”
Section: Introductionmentioning
confidence: 99%